Living donor hepatectomy in medium volume liver transplant centre has comparable outcomes to high volume centres: validation of donabedian quality assurance framework. Issue 4 (April 2022) - Yeow, Marcus Wei Xuan; Pang, Ning Q.; Bonney, Glenn K.; Madhavan, Krishnakumar; Kow, Wei Chieh Alfred; Iyer, Shridhar Ganpathi
Abstract: Background: Given the complexity of living donor hepatectomy, it is expected that high hospital volume will better outcomes. This study aims to evaluate post-operative outcomes for living donor hepatectomy in a medium volume liver transplant centre and compare to outcomes in high volume centres. Also, it serves as a validation tool for framework of structure-process-outcome model for safe living donor hepatectomy program. Methods: 204 donors who underwent donor hepatectomy between June 1996 to September 2019 were reviewed retrospectively and compared to outcomes in high volume centres. Results: At 6 months, overall donor morbidity rate was 20/204 (9.8%). Wound complications were most common at 5/204 (2.5%). Majority of complications were either Clavien grade 1 or 2 and only 3 donors had Clavien grade 3 complications. There was zero donor mortality. Discussion: Our centre's donor morbidity rate of 9.8% is the one of the lowest reported in the published literature. With increased experience, stringent donor selection and enhanced perioperative care by a multi-disciplinary team, outcomes in a medium volume centre can match the outcomes reported in high volume centres. The framework for quality in terms of structure, process and outcomes is presented which can be adopted for developing programs.